Psychological Aspects of Management and Economics of Higher Education - Glyzina, Maria P.; Telesh, Andrey D.; Muradova, Safura S.; Chernykh, Anatoly I.; Smolentsev, Vitaly M.; Koroleva, Elvira V. (International Journal of Economics and Financial Issues, 2016)
This paper considers the idea that the creative productivity of and psychological basis for achieving high results is expressed in general abilities, creativity, optimism, belief in success and motivation in all social spheres. Management education is crucial for the formation of future professionals in all areas of public life. The article contains analysis of development of new progressive models of management education which should combine the basic types of controls: administrative (command) and motivational management, project management and process management. To control dynamics, which was considered more “progressive”, there are two problems. The first is the problem of the relation of design (innovation) and process (recurring) activities, the other activities of education authorities, particularly at the municipal level, a significant proportion of time and energy which is the current routine functions - the payment of salaries to employees of educational institutions, etc. In the modernization models of management education need to move from the traditional use of two control mechanisms - planning (many “activities”), and pervasive control for the full set (cycle) mechanisms, such as: analysis of current state controlled educational system, the forecast of development of the education system, goal setting, scheduling development tasks, providing resources, monitoring the development of the educational system, which is the essence of operational management. Keywords: higher education, psychology, management of education, modernization of education, economic education JEL Classifications: A20, A29, I21, I29